2012
DOI: 10.1177/0954406212469323
|View full text |Cite
|
Sign up to set email alerts
|

Particle image velocimetry studies on the swirling flow structure in the vortex gripper

Abstract: In this article, particle image velocimetry was used to measure the two-dimensional flow field for vortex gripper. The vortex gripper was divided into two parts for respective research, including vortex cup and the gas film gap. In the part of vortex cup, the tangential velocity increases gradually, and the velocity decreases intensely in the vicinity of the vortex cup's wall after it reaches maximum. In addition, the velocity decreases gradually with the increase of the gas film gap. In the part of gas film g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Hence, the plate can also be moved up and down in the vertical direction. The laser meter located under the plate can continuously detect the position of the plate in the vertical direction and we then obtain the value of h. In the course of the experiment, the following steps were followed: (1) the feeding bolt was adjusted to bring the gripper into contact with the upper surface of the plate; (2) three locating pins were set and their ends were allowed to contact with the vortex gripper; (3) clamps were locked to hold the pins tightly; (4) spring was compressed and held in compression using the spring stopper; (5) laser meter was reset to zero; (6) given flow was supplied to the vortex gripper; (7) height of the clearance was continuously increased to obtain suction force F from the force sensor under different h conditions, and the measured data were recorded through data acquisition (DAQ).…”
Section: Measurement Of Suction Forcementioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the plate can also be moved up and down in the vertical direction. The laser meter located under the plate can continuously detect the position of the plate in the vertical direction and we then obtain the value of h. In the course of the experiment, the following steps were followed: (1) the feeding bolt was adjusted to bring the gripper into contact with the upper surface of the plate; (2) three locating pins were set and their ends were allowed to contact with the vortex gripper; (3) clamps were locked to hold the pins tightly; (4) spring was compressed and held in compression using the spring stopper; (5) laser meter was reset to zero; (6) given flow was supplied to the vortex gripper; (7) height of the clearance was continuously increased to obtain suction force F from the force sensor under different h conditions, and the measured data were recorded through data acquisition (DAQ).…”
Section: Measurement Of Suction Forcementioning
confidence: 99%
“…The vortex gripper does not make any contact with the sucked surface and is not easily susceptible to the surface roughness; these are its significant features in comparison with the conventional vacuum suction cup. These features make the vortex gripper suitable for some special occasions, for example, transferring and handling of semiconductor wafers and liquid crystal glass substrates 6 and capturing of rough-surfaced workpieces. 7 Although the vortex gripper possesses a simple structure, its internal flow is more complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iio et al 33 observed the form of the vortex flow in an underwater environment in 2010. Moreover, in 2013, Wu et al 34 obtained experimental data on velocity distribution using visual equipment and the particle image velocimetry method and proposed several empirical formulae for the velocity distribution in vortex flow. However, the development of the simplified mathematic model remains a rather difficult work because of vortex flow complication.…”
Section: New Mechanism Based On Vortex Adhesionmentioning
confidence: 99%
“…By using visualization methods, Iio et al observed the vortex flow inside the vortex chamber in an underwater condition (Iio et al, 2010). Wu et al analyzed the velocity distribution in the vortex chamber through the use of visual equipment and particle image velocimetry (Wu et al, 2013). Building upon their prior work, Li et al analyzed the velocity and pressure fields inside a vortex gripper in detail using numerical fluid dynamics calculations and exposed the relationship between them (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%